Routing Strategies and Buffer Management in Delay Tolerant Networks - K. Ahmed, Kawakib; Omar, Mohd Hasbullah; Hassan, Suhaidi (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
The Delay Tolerant Networks (DTN) is an intermittently connected network that enables communication among wireless nodes in the heterogeneous environments where end-to-end connectivity between nodes does not exist. These networks are characterized by a long delay, asymmetric data rate and low data rate. DTN uses store and forward mechanism to transmit messages from the source node to destination node. Routing in DTN is challenging because of frequent and long duration periods of disconnectivity. Therefore, the selection of routing protocol in DTN depends on the application environment in which it is used. This study presents a comprehensive survey on DTN and brief outlines of popular routing protocols in DTN. This paper also highlights the buffer management technologies that are used in DTN. Where an efficient buffer management scheme is required to choose at each step which of the messages should be transmitted in case of limited bandwidth and which of the messages should be dropped when the buffer is full. Regardless of which routing algorithms used.